Coal Post-Mining Reclamation Policies in Several Countries: Lessons for Indonesia - Wicaksono, Muhammad Bagus Adi; Triasari, Devi (Journal of Law, Environmental and Justice, 2024)
This study seeks to delineate coal post-mining reclamation regulations in the United States, Australia, and China. Subsequent analyses are performed to enhance the control of coal post-mining reclamation in Indonesia. This research employs a comparative and conceptual law approach that aligns with the research aims. The findings indicate that in the United States and China, coal reclamation and post-mining arrangements are executed through guarantees in the form of cash or bonds, governed by specific legislation, and overseen by designated institutions with the authority to manage post-mining reclamation responsibilities while facilitating public involvement in the planning of coal post-mining reclamation initiatives. Indonesia needs more specific legal legislation controlling coal post-mining reclamation guarantees and a designated agency empowered to manage post-mining reclamation responsibilities